A design of underwater soft gripper with water pressure sensing and enhanced stiffness. Issue 2 (26th February 2023) - Huang, Jingke; Wang, Zhanhua; Li, Jianda; Tang, Zhijie
Abstract: In this paper, a hydraulic soft gripper for underwater applications is designed to provide a solution for improving the gripping force as well as the sensing capability of the soft gripper. The soft gripper is made of silicone and has an integrated semi-circular hydraulic network inside. To enhance the rigidity and grasping performance of the soft gripper, we have integrated a restriction layer consisting of a spring steel plate in the soft gripper. Meanwhile, to enhance the sensing capability of this soft gripper, we have designed a water pressure sensor based on resistance strain gauges and integrated it on the spring steel plate. Before fabrication, we determined the structural parameters of the soft gripper by geometric analysis. Then we experimentally evaluated its pressure-bearing capacity, bending performance, the role of spring steel plates, and the accuracy of the sensor.The experimental results show that the spring steel plate improves the gripping force of the soft gripper, the sensor also has high accuracy, and the built four-finger gripping system has good adaptability to objects of different shapes and weights.Compared with the existing solutions, this solution takes a simpler structural form while improving the gripping force and sensing ability of the soft gripper, and integrates the issues of improving the gripping force and sensing ability. The spring steel plate used in this paper not only improves the gripping force of the soft gripper but also provides a stable and reliable platform for installing sensors.